1991
DOI: 10.1212/wnl.41.4.566
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of transcranial cortical magnetic stimulation in detecting pyramidal tract lesions in clinically definite multiple sclerosis

Abstract: We determined central motor conduction time (CMCT) (motor cortex to root C-8 and motor cortex to root S-1) as well as the amplitude of the compound muscle action potentials in the hypothenar and the abductor hallucis muscles on both sides in 44 patients with definite MS. We compared the values with standards obtained from 86 healthy controls and correlated them with the degree of clinical deficit of the limbs examined. Thirty-nine patients (88.6%) showed a prolonged CMCT. By comparison, only 74.4% of patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 0 publications
5
34
0
1
Order By: Relevance
“…This is entirely in keeping with our observations that CFS patients are supersensitive to ACh and show an exaggerated GH release response when challenged with pyridostigmine, an acetylcholinesterase (AChE) inhibitor that increases intrasynaptic ACh (Chaudhuri et al, 1997a). The recent reports of prolonged central motor conduction time in both CFS and MS (Hilgers et al, 1998;Ravenborg et al, 1992;Mayr et al, 1991) are again further evidence for a common pathogenic mechanism of fatigue. These data, together with our research ®ndings of abnormal REE in CFS, transient low level antibodies to voltage-gated potassium channels in the sera of 25 per cent of CFS patients and the relationship between CTX and the development of CFS, cannot be explained rationally except as a channelopathy.…”
Section: Is Cfs An Acquired Channelopathy?supporting
confidence: 88%
“…This is entirely in keeping with our observations that CFS patients are supersensitive to ACh and show an exaggerated GH release response when challenged with pyridostigmine, an acetylcholinesterase (AChE) inhibitor that increases intrasynaptic ACh (Chaudhuri et al, 1997a). The recent reports of prolonged central motor conduction time in both CFS and MS (Hilgers et al, 1998;Ravenborg et al, 1992;Mayr et al, 1991) are again further evidence for a common pathogenic mechanism of fatigue. These data, together with our research ®ndings of abnormal REE in CFS, transient low level antibodies to voltage-gated potassium channels in the sera of 25 per cent of CFS patients and the relationship between CTX and the development of CFS, cannot be explained rationally except as a channelopathy.…”
Section: Is Cfs An Acquired Channelopathy?supporting
confidence: 88%
“…13,15,19,25 They are useful for monitoring disease activity in patients with primary and secondary progressive MS 17 and may help predict the natural evolution of the disease. 9 However, little is known of the utility or otherwise of MEPs in experimental autoimmune encephalomyelitis (EAE), a preclinical model of MS with motor system involvement that can be induced in various strains of rodents.…”
Section: Accepted 14 September 2005mentioning
confidence: 99%
“…In addition, the reported diagnostic sensitivities of iSP measurements showed large variation, ranging from 80% in early RRMS [14] and 74% in a mixed sample of RRMS and chronic progressive MS [13] to 46% in a mixed sample of RRMS and secondary progressive MS [12]. In contrast, TMS measurements of central motor conduction time (CMCT) are now a diagnostic standard to assess the integrity of the corticospinal tract in patients with definite MS, and many studies reported consistently diagnostic sensitivities between 60% and 80% for both upper and lower limbs [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%